Endovascular mechanical thrombectomy and stenting in a case of central vein thrombosis. Issue 2 (18th February 2021) - Vijayvergiya, Rajesh; Kaur, Navjyot; Sahoo, Saroj K; Sharma, Ashish
Abstract : Central vein stenosis and thrombosis are frequent in patients on haemodialysis for end-stage renal disease. Its management includes anticoagulation, systemic or catheter-directed thrombolysis, mechanical thrombectomy and percutaneous transluminal angioplasty (PTA). Use of mechanical thrombectomy in central vein thrombosis has been scarcely reported. We hereby report a case of right brachiocephalic vein thrombosis with underlying stenosis, which was successfully treated by mechanical thrombectomy followed by PTA and stenting. The patient had a favourable 10 months of follow-up.